ROLE OF HOT MACHINING TECHNIQUE ON MACHINABILITY ENHANCEMENT FOR HARDENED STEELS - SYHOOD, MAHA SATTAR; MOHAMMED, KAMAL ABDULKAREEM; AL-AMEEN, EHSAN SABAH (Journal of Duhok University, 2023)
This paper investigates the effects of cutting factors on surface roughness of hardened steel work piece in hot machining process with heating temperature of (150 and 250) ºC, including depth of cut, feed rate, and cutting speed. The experimental side made use of the flam method. The work highlights the advantages of hot machining and how it can be used effectively on materials that are challenging to cut. The best results were obtained with the recommended cutting parameters of 90.64 m/min cutting speed, cutting feed rate of 0.64 mm/rev, and cutting depth by 1 mm at 250 oC.